2018
DOI: 10.3390/ijms19092682
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Expression of Hedgehog Pathway Components in a Large Panel of Human Tumor Cells and Inhibition of Tumor Growth by GANT61: Implications for Cancer Therapy

Abstract: The sonic Hedgehog/GLI signaling pathway (HH) is critical for maintaining tissue polarity in development and contributes to tumor stemness. Transcription factors GLI1–3 are the downstream effectors of HH and activate oncogenic targets. To explore the completeness of the expression of HH components in tumor cells, we performed a screen for all HH proteins in a wide spectrum of 56 tumor cell lines of various origin using Western blot analysis. Generally, all HH proteins were expressed. Important factors GLI1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…Although we observed a positive antitumor effect of GANT61 on cell viability, the impact seemed to be relatively weak compared with that observed in other type of cancers. For instance, previous studies reported that only 10%-40% of cells remained viable after treatment with 10-20 µM of GANT61 in lung, melanoma, prostate, glioma, and breast cancer cells [23][24][25][26][27][28][29]. These reports and our observation allow us to hypothesize that the GANT61 target may be a small subpopulation in HLE and HLF cells.…”
Section: Discussionsupporting
confidence: 77%
“…Although we observed a positive antitumor effect of GANT61 on cell viability, the impact seemed to be relatively weak compared with that observed in other type of cancers. For instance, previous studies reported that only 10%-40% of cells remained viable after treatment with 10-20 µM of GANT61 in lung, melanoma, prostate, glioma, and breast cancer cells [23][24][25][26][27][28][29]. These reports and our observation allow us to hypothesize that the GANT61 target may be a small subpopulation in HLE and HLF cells.…”
Section: Discussionsupporting
confidence: 77%
“…GLI3 shows the most consistent expression in all cell lines in the full-length form (GLI3FL), while in some cell lines, it can also be found in the repressor form (GLI3R). Other authors have also detected the expression of GLI proteins in some of the melanoma cell lines we used in our study (MEWO, SKMEL2, MEL501, SKMEL3, and RMPI-7951) [ 28 ]. BRAF or NRAS mutation status is not correlated with the differences in protein or gene expression between the cell lines, but KRAS mutated MEL505 cell line shows lower gene expression levels for all tested genes ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 86%
“…There are different mechanisms that can activate a variety of signaling pathways, thereby bypassing the effect of BRAF inhibition. It is already known that the HH-GLI signaling pathway is active in melanoma [ 11 , 12 , 28 , 104 ]. Here, we confirm HH-GLI pathway activity in 14 melanoma cell lines with different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that inhibition of GLI function holds strong potential to become a novel, clinically effective approach to treat malignant sarcoma. In recent years, the small molecule inhibitor GANT61 is the most widely appreciated drug target of the GLI1/2, with improved potency and chemical stability, has strong and extensive antitumor effects in pancreatic cancer, breast cancer, rhabdomyosarcoma, Glioblastoma, myeloid leukemia, osteosarcoma, melanomas, and so on 24,25 . GANT61 killed the sensitive tumor cells through antiproliferation, oxidative stress, apoptosis, and autophagy, DNA damage, modulate the radiosensitivity and migration of cancer cells 26,27,28,29 .…”
Section: Discussionmentioning
confidence: 99%